Synthesis and characterization of self-cleaning hydrophobic organic coating / Amirul Syafiq Abdul Jaafar - Amirul Syafiq , Abdul Jaafar (2020)
Three self-cleaning coating systems namely Polydimethylsiloxane (PDMS)/Sylgard, PDMS/3-Aminopropyltriethoxysilane (APTES) (tagged as A1) and A1 blended with nano-Calcium Carbonate (CaCO3) have been synthesised on glass substrates via dip-coating and spray-coating techniques. All of the prepared coatings were dried under ambient condition before being subjected to characterisations and testing(s). The effect of various weight percentages of Sylgard resin that are 5wt.% (S1 coating), 10wt.% (S2 coating), 15wt.% (S3 coating), and 20 wt.% (S4 coating) on the hydrophobicity, self-cleaning property, anti-fog performance and mechanical property of PDMS/Sylgard coating have been discussed in the first section of this thesis. The PDMS/Sylgard coated glass substrates exhibit transmittance above 94% in UV-Vis region, indicating high transparency. From the micro-scratch and micro-hardness tests, it was observed that the PDMS/Sylgard coating possess of stronger adhesion to glass substrate as the Sylgard concentration increased suggesting that the surface became stiffer with greater Sylgard concentration in PDMS matrix. The Water Contact Angle (WCA) showed that hydrophobicity of PDMS/Sylgard coated glass increased with increasing weight percentage of Sylgard up to 10 wt. %. When the weight percentage was above 15 wt. %, the WCA started to decrease due to saturated Si-O-Si crosslinking. In addition, the S2 coating showed an excellent anti-fog performance and great self-cleaning behavior where its transparency was above 64% after exposed to outdoor environment for 4 months. Thereafter, the best composition of S2 resin (10 wt.% Sylgard) was blended with the APTES ( A1 matrix) and different weight ratios of nano-Calcium Carbonate (CaCO3) that are 0.2wt.% (C1 coating), 0.4wt.% (C2 coating), 0.6wt.% (C3 coating), 0.8wt.% (C4 coating), 1.0wt.% (C5 coating) and 1.2wt.% (C6 coating) that have been discussed in the second section of this work. Both A1 coating and A1 blended with nano-CaCO3 coating systems exhibit high transmission above 83% in UV-VIS region. The consolidation of nano-CaCO3 in A1 matrix significantly improved the WCA of coating system since embedded nano-CaCO3 intensifies A1 surface roughness. The hydrophobicity of A1 blended with nano-CaCO3 coating systems increases with increasing of wt. % of nano-CaCO3 up to 0.8 wt. %. As the weight percentages was increased above 0.8wt%, WCA of A1/nano-CaCO3 coating system reduces to lower value due to agglomerations of nanoparticles at high nano-CaCO3 loading rates. The A1 blended with nano-CaCO3 coating systems exhibit stronger adhesion to glass substrate as weight percentages of nano-CaCO3 increased up to 0.8 wt.%. However, the A1 blended with nano-CaCO3 coating systems displayed weaker adhesion at high loading rates of nano-CaCO3 mainly above 0.8wt.% because higher loading rates of nanoparticles in A1 matrix lead to more crystalline surface and more crystalline surface make the surface become more brittle. Due to high hydrophobicity, the C4 coating exhibit the best anti-fog performance and achieves great self-cleaning effect among A1 blended with nano-CaCO3 coating systems under outdoor environment where its transparency was above 74% after exposed to outdoor environment for 4 months. Overall, all three coating systems retained their hydrophobicity after prolonged outdoor environment, revealed that prepared coatings systems have strong durability against rainfall impact..